Chlorophyll and chlorophyll derivatives interfere with multi-drug resistant cancer cells and bacteria - Wang, Erjia; Braun, Markus S.; Wink, Michael (Molecules, 2019)
Multidrug resistance (MDR) causes challenging tasks in medicine. Human cancer cells, as well as microorganisms, can acquire multiresistance due to the up-regulation of efflux pumps (ABC transporters) and are difficult to treat. Here, we evaluated the effects of chlorophyll, the most abundant pigment on the globe, and its derivative, pheophytin, on cancer cells and methicillin-resistant Staphylococcus aureus (MRSA). We found that both substances have significant reversal effects on multidrug-resistant CEM/ADR5000 cells (RRpheophytin = 3.13, combination index (CI)pheophytin = 0.438; RRchlorophyll = 2.72, CIchlorophyll < 0.407), but not on drug-sensitive CCRF-CEM cells when used in combination with doxorubicin. This indicates that the porphyrins could interact with efflux pumps. Strong synergism was also observed in antimicrobial tests against MRSA when combining ethidium bromide with chlorophyll (FICI = 0.08). As there is a strong need for new drugs in order to reliably treat MDR cells, our research provides potential candidates for further investigation.
Gesehen am 11.12.2019